Analisis Fundamental Makro Terhadap Nilai Perusahaan Ddengan Struktur Modal, Kinerja Keuangan, Struktur Kepemilikan Sebagai Variabel Perantara pada Beberapa Perusahaan Energi - Handoko, StevenNathanael; Hwihanus (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research functions to find out what variables can influence company value. The variables are macro fundamentals, capital structure, financial performance, and ownership structure which influence company value. This research takes secondary data from the Indonesian stock exchange. The companies used for the sample are energy companies in Indonesia from 2018 to 2023.